2017
DOI: 10.14573/altex.1605041
|View full text |Cite
|
Sign up to set email alerts
|

3-D nasal cultures: Systems toxicological assessment of a candidate modified-risk tobacco product

Abstract: ratory animals -to reduce the number of animals, to refine the design of procedures such that pain and distress are minimized, and to replace animal models with alternative methods and lower organisms when possible (Doke and Dhawale, 2015). In this regard, the capability to preserve human respiratory cells in culture provides a tool not only to generate mechanistic data, but also to improve the predicted effects of exposure hazard through inhalation in humans. An emphasis on assessment studies using human-deri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 62 publications
1
35
0
Order By: Relevance
“…Targeted proteomics by PRM was conducted at the 24 h PE time for the ALI buccal epithelial cultures (N = 9 independent exposure experiments), and at the 48 h PE time for the ALI small airway epithelial cultures (N = 9 independent exposure experiments) following a previous published protocol (Iskandar et al 2017). The timepoint collection for each culture type was decided based on the previous studies in which we detected greater changes in the protein levels following exposure (data not shown).…”
Section: Targeted Proteomics By Prmmentioning
confidence: 99%
See 1 more Smart Citation
“…Targeted proteomics by PRM was conducted at the 24 h PE time for the ALI buccal epithelial cultures (N = 9 independent exposure experiments), and at the 48 h PE time for the ALI small airway epithelial cultures (N = 9 independent exposure experiments) following a previous published protocol (Iskandar et al 2017). The timepoint collection for each culture type was decided based on the previous studies in which we detected greater changes in the protein levels following exposure (data not shown).…”
Section: Targeted Proteomics By Prmmentioning
confidence: 99%
“…Raw files from the PRM acquisition were analyzed with SpectroDive (version 8.0 Biognosys AG). Ion chromatograms for the endogenous peptides and the corresponding stable isotope-labeled reference peptides were extracted for all measured transitions [the list of transitions was reported in a previous publication (Iskandar et al 2017)] using the software vendor's default settings. For quantification, the area under the curve (AUC) intensities of all transitions were summed, and ratios of AUC sums of the endogenous and corresponding reference peptide signal were calculated.…”
Section: Targeted Proteomics By Prmmentioning
confidence: 99%
“…Although current systems toxicology studies reported a lesser impact of e-cigarette and heated tobacco aerosols in vitro 5, 6 , other toxicological studies using targeted endpoints reported potential for DNA damage, oxidative stress and cytotoxicity 12, 13 . These discrepancies arise from the use of different cell models, products/devices, exposure matrices, times, and doses.…”
Section: Introductionmentioning
confidence: 96%
“…Examples of robust in vitro assessment studies of novel nicotine delivery devices (heated tobacco products and e-cigarettes) have used a relevant cell model, a well-considered exposure strategy combined with holistic untargeted omics screens to comprehensively assess the biological perturbations 5, 6 . Such in vitro- based systems toxicology approaches have been driven by the increasing demand to replace the use of low-throughput animal testing with high- throughput in vitro and computational technologies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation